Surface hardness measurement of NiP-plated AA7050 - Sungmo Moon(문성모); Juseok Kim(김주석) (Biuletyn Uniejowski, 2021)
This paper is concerned with the surface hardness measurement of NiP-coated AA7050 using different loads from 10 to 100 g. The surface hardness was observed to increase from 180 to 600 Hv with increasing NiP layer thickness, depending on the load applied for indentation. When NiP coating thickness is thinner than 2 ㎛, the surface hardness of NiP-coated AA7050 was mainly determined by AA7050 substrate, while it was significantly increased by NiP coating layer when NiP coating thickness is thicker than 2 ㎛. Hardness of AA7050 substrate itself was not dependent on the applied load but the hardness of NiP-coated AA7050 was largely influenced by the load applied for indentation. The largest difference of hardness between 10 g and 100g of applied loads, was obtained at the NiP thickness of about 8 ㎛ above which the measured hardness at 10 g reached a maximum value of about 600 Hv. It was also observed that indentation-induced plastic deformation next to the indented zone occurs when NiP layer is 5.64 times thicker than the depth of impression formed by indentation. KCI Citation Count: 0